Analisa Risiko Menggunakan Metode Likelihood Dan Consequence Risk Matriks - Lutvi, Rival; Rachmadhani, Mirga Maulana; Tosofu, Angga Zulfikar; Mbisikmbo, Mines; Supriatna, Intan Iriani (Universitas Muhammadiyah Sorong, 2024)
CV. Tunggal is located in the Aimas district. This research discusses risk analysis in laying hen farming businesses using the Likelihood and Consequence Risk Matrix method. This method combines the criteria for the likelihood of a risk occurring (likelihood) and the resulting impact (consequence) to quantify and prioritize risks. Data was obtained through surveys and direct interviews with respondents as well as literature studies from various sources. Data analysis was carried out using Descriptive Analysis. The identification results show that there are twenty main risks divided into operational, financial, strategic and fraud categories. These risks are then analyzed and scored based on their level of likelihood and impact. The findings show that A4 related to uncertain sales, A7 limited medicines for chickens, A12 unstable supply and demand, and A16 Difficulty in getting capital and business partners are the highest risks and require immediate mitigation measures. Recommended mitigations are A4 sales data analysis, marketing stock management, A7 inventory of medicines and vitamins for chickens, A12 analyzing the market for eggs coming in from outside the region, and A16 increasing relations with shops and distribution agents. By implementing this mitigation strategy, it is hoped that yam farming businesses can reduce the negative impacts of identified risks and increase operational efficiency and business sustainability. This research provides significant insight for chicken farming business owners and researchers in the field of small and medium enterprise risk management.